Adoção na velhice: limites e possibilidades - Vale, Camile Biscola do (2013)
This work discusses the possibility of adopting children and adolescents by elderly people. In the first chapter there is a theoretical discussion about concepts of old age and aging, taking into account the notion of culture and how this culture indicates a large heterogeneity on issues related to old age and aging. Some examples of elders who exert or wish to exercise paternity and maternity through artificial insemination or adoption are highlighted. The second chapter focuses on adoption, its history and evolution in Brazil, reaching the current legislation defining cases for adoption. Taking into account that the legislation that guides and defines the case for adoption is the Child and Adolescent Statute (ECA), this statute does not define a maximum age for applicants interested in adoption. In the third chapter, the issue of old age and adoption appear united and there is an analysis of how the assessments of elders interested in adoption are conducted. This dissertation interprets how social workers of the Forums in the ABCD region - Santo André, São Bernardo, São Caetano do Sul and Diadema - who mediate the assessment processes for the qualification of elderly adopters, interpret the paternity and maternity of children and adolescents in the old age